V is for vengeance - Grafton, Sue (New York : G.P. Putnam's Sons, 2011)
California PI Kinsey Millhone investigates the death of Audrey Vance, a woman she helped arrest for shoplifting, and antagonizes just about everyone, including Audrey's fianc several loan sharks, a stone-cold killer, and a hapless burglar who knows more than is healthy for him.
'A Marian Wood book.'
Keywords: Millhone, Kinsey (Fictitious character) -- Fiction; Women private investigators -- California -- Fiction; Theft -- Fiction; Organized crime -- Fiction; Murder -- Fiction; Revenge -- Fiction